2019
DOI: 10.1021/acs.iecr.8b03958
|View full text |Cite
|
Sign up to set email alerts
|

Amine Modification of Binder-Containing Zeolite 4A Bodies for Post-Combustion CO2 Capture

Abstract: In the current study, a new type of composite adsorbent was synthesized by amine modification of binder-containing zeolite 4A bodies and its potential application in the post-combustion CO2 capture was evaluated. A wide range of aliphatic straight chain amines such as propylamine (PA), butylamine (BA), pentylamine (PEA), and their respective branched chain amines, iso-propylamine (IPA), iso-butylamine (IBA), and iso-pentylamine (IPEA), were used in a smaller fraction to modify binder-containing zeolite 4A bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 93 publications
3
30
0
Order By: Relevance
“…Combined with the current experimental results and previous studies, 9 , 52 54 a plausible carbon dioxide adsorption mechanism is proposed and shown in Figure 10 . After immobilization of PEI, SiO 2 adsorbents have more active adsorption sites (e.g., −NH 2 ).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Combined with the current experimental results and previous studies, 9 , 52 54 a plausible carbon dioxide adsorption mechanism is proposed and shown in Figure 10 . After immobilization of PEI, SiO 2 adsorbents have more active adsorption sites (e.g., −NH 2 ).…”
Section: Resultssupporting
confidence: 80%
“…19 , 20 As mentioned above, mesoporous silica is widely used as a support to immobilize amines due to its good thermal stability, high pore volume, and abundance of surface silica hydroxyl groups. 9 , 21 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Mg-MOF-74 also showed structural degradation in the presence of moisture. In comparison, a variety of amine-functionalized adsorbents have already been shown to have a high CO 2 /N 2 selectivity. In the work presented by Kumar et al, tetraethylenepentaamine (TEPA)-impregnated SBA-15 preformed significantly better, achieving a CO 2 uptake of 158 mg/g when exposed to an air stream at 49% relative humidity (RH) and 23 °C for 12 h. This is in agreement with a number of studies that incorporated polyethylenimine (PEI) in sorbents for DAC conditions, reporting similar CO 2 adsorption and selectivity. Sayari et al showed that under certain adsorbent synthesis conditions, an amine efficiency of ∼308 mg of CO 2 /g PEI can be achieved for an air stream at 49% RH.…”
Section: Introductionsupporting
confidence: 67%
“…Further, a good agreement of the Sips fitting parameters www.nature.com/scientificreports/ with the experimental data (R 2 ∼ 0.99) suggest the efficient interaction of CO 2 molecules with the pore wall of RHA-MIL-101(Cr), due to the heterogeneity in the adsorbent surface (Fig. S10, Table S2) 45,46 . Concurrently, the adsorption of N 2 is found to be least in the case of RHA-MIL-101(Cr)-II as compared to RHA-MIL-101(Cr)-I and MIL-101(Cr) (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…Further, the CO 2 /N 2 selectivity of 18 observed for RHA-MIL-101(Cr)-II is significantly higher as compared to MIL-101(Cr) (CO 2 /N 2 selectivity = 7). The observed more than two-fold enhancement in CO 2 /N 2 selectivity for RHA-MIL-101(Cr)-II could be a consequence of the exceptionally larger polarizability and quadrupole moment of CO 2 (29.11 × 10 -25 cm −3 and 4.30 × 10 −26 esu −1 cm −1 , respectively) than that of N 2 (17.40 × 10 −25 cm −3 and 1.52 × 10 −26 esu −1 cm −1 , respectively) and the steric effect of adsorbing molecules (CO 2 , N 2 ) on the adsorbent surface 45 . Notably, micropore size distribution obtained from CO 2 adsorption isotherm at 0 °C, also inferred the generation of new ultra-micropores (pore diameter of 0.35 nm) in RHA-MIL-101(Cr)-II ( Fig.…”
Section: Resultsmentioning
confidence: 98%